Pengaruh Strategi Reward Terhadap Motivasi Belajar IPAS Materi Ekosistem Siswa Sekolah Dasar - Dini Triwulandari; Laili Rahmi (Jayapangus Press, 2026)
This study was motivated by the low learning motivation of fifth-grade students in the Natural and Social Sciences (IPAS) subject, particularly on ecosystem material, which was reflected in their limited interest, attention, persistence, and participation during lessons. This study aimed to examine the effect of a reward-giving strategy on students' learning motivation in IPAS ecosystem material at SD Negeri 160 Pekanbaru. A quantitative approach was applied using a pre-experimental one-group pretest-posttest design involving 29 fifth-grade students selected through saturated sampling. Data were collected through a learning-motivation questionnaire on a four-point Likert scale, supported by observation and teacher interviews. The results showed that the average motivation score increased from 42.34 in the pretest to 57.76 in the posttest, and the paired sample t-test indicated a significant difference between the scores before and after the treatment (p < 0.001). Because the design did not include a control group, this finding is interpreted as a significant improvement in students' motivation following the reward treatment rather than as strong causal evidence. These findings suggest that reward can serve as a promising pedagogical strategy for strengthening elementary students' learning motivation.